Guratan Makna Sosial dan Religius Lagu Ongko Koe dalam Guyub Tutur Manggarai di Flores - Fransiskus Butan; Simon Sabon Ola (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2010)
This study examines the social and religious meanings of Ongko Koe folksong in Manggarai speech community. The data for the research were obtained from observation, interview, recording, note-taking, and documentation. The results show that from a social point of view, Ongko Koe folksong deals with the perception of Manggarai speech community of the importance of the maintenance of unity, especially in term of wa'u as patrilinear-genealogic clan. From a religious point of view, it deals with the perception of Maggarai speech community of the existence of the Supreme God and ancestors as moral sources determining the sustainability of human life in this world. The study suggests that Ongko Koe folksong should be maintained in order to retain its social and religious meaning for Manggarai speech community.